What makes customer purchase intention for hypermarket products in Malaysia? - Haque, A. K. M. Ahasanul; Masnoon, Tasvin; Rahman, Mohammad Moshiur (2022)
This study intends to discover factors affecting customers’ purchase intention to visit hypermarkets in Malaysia. The primary objective of this study is to understand the variables that affect customers’ hypermarket buying intention. Therefore, it will examine the relationships between TPB model variables and buying intention. It is determined that the suggested theory of planned behaviour (TPB) is suitable for predicting customer intention and examining the relationships between variables. The quantitative method and convenience sampling technique will be used for this study with a maximum of 300 participants using a structured questionnaire through an online survey. Data analysis will begin with an assessment of the demographic characteristics of the respondents and shift to descriptive statistics. The hypotheses will be tested using regression analysis through SPSS statistical analysis program. Finally, this study will provide valuable insight into the growing number of hypermarket sectors requiring in-depth investigation and assistance to the management in establishing strong client relationships.